Chromium-reducible sulfur (CRS) as proxy for pyrite from a sediment core from upper intertidal site T5-2 in the Gulf of Carpentaria, Australia - James Z Sippo (PANGAEA, 2021)
A massive mangrove tree dieback event occurred in 2015/2016 along ~1000 km of pristine coastline in the Gulf of Carpentaria, Australia. We present chromium-reducible sulfur (CRS) data of a sediment core (ca. 1 m depth) from site T5-2 in the upper intertidal zone in the region of living Avicennia marina.